Improving Health Care in Low- and Middle-Income Countries A Case Book - Marquez, Lani Rice (Springer Nature, 2020)
This open access book is a collection of 12 case studies capturing decades of experience improving health care and outcomes in low- and middle-income countries. Each case study is written by healthcare managers and providers who have implemented health improvement projects using quality improvement methodology, with analysis from global health experts on the practical application of improvement methods. The book shows how frontline providers in health and social services can identify gaps in care, propose changes to address those gaps, and test the effectiveness of their changes in order to improve health processes and outcomes. The chapters feature cases that provide real-life examples of the challenges, solutions, and benefits of improving healthcare quality and clearly demonstrate for readers what quality improvement looks like in practice: Addressing Behavior Change in Maternal, Neonatal, and Child Health with Quality Improvement and Collaborative Learning Methods in Guatemala Haiti's National HIV Quality Management Program and the Implementation of an Electronic Medical Record to Drive Improvement in Patient Care Scaling Up a Quality Improvement Initiative: Lessons from Chamba District, India Promoting Rational Use of Antibiotics in the Kyrgyz Republic Strengthening Services for Most Vulnerable Children through Quality Improvement Approaches in a Community Setting: The Case of Bagamoyo District, Tanzania Improving HIV Counselling and Testing in Tuberculosis Service Delivery in Ukraine: Profile of a Pilot Quality Improvement Team and Its Scale‐Up Journey Improving Health Care in Low- and Middle-Income Countries: A Case Book will find an engaged audience among healthcare providers and administrators implementing and managing improvement projects at Ministries of Health in low- to middle-income countries. The book also aims to be a useful reference for government donor agencies, their implementing partners, and other high-level decision makers, and can be used as a course text in schools of public health, public policy, medicine, and development. ACKNOWLEDGMENT: This work was conducted under the USAID Applying Science to Strengthen and Improve Systems (ASSIST) Project, USAID Award No. AID-OAA-A-12-00101, which is made possible by the generous support of the American people through the U.S. Agency for International Development (USAID). DISCLAIMER: The contents of this book are the sole responsibility of the Editor(s) and do not necessarily reflect the views of USAID or the United States Government. Presents real-life case studies, from all levels of the healthcare system and addressing a wide range of health topics, to teach readers about using quality improvement methodology to strengthen health care in lower- and middle-income countries Teaches readers about the process of designing improvement efforts, choosing priorities, carrying out activities, understanding results, building health worker capacity to improve care, engaging leadership, and applying lessons learned from improvement to spread and scale-up initiatives Provides rich detail on how improvement work is applied in practice rather than focusing on methodologies and theory Includes expert commentaries and analysis to guide the reader in understanding results on key issues and themes in designing, supporting, and scaling up improvement Open access